A new species of Deutella Mayer 1890 (Crustacea: Amphipoda) from the Mexican Pacific coast - Alarcón-Ortega, Lucy C.; Carballo, José L. (Zootaxa, 2019)
A new species of caprellid, Deutella mazatlanensis n. sp., is described from Mazatlán Bay, (east Pacific México). Deutella mazatlanensis was found associated with bryozoans, hydroids and sponges in shallow waters. The new species can be differentiated from the remaining species of the genus mainly by the dorsal, anteriorly directed projection on the head; the two dorsal projections and a lateral acute projection anteroventrally projected on pereonite 2 and gnathopod 2 in males. The presence of this species on the Mexican Pacific coast, constitutes the fourth report of Deutella genus for the Pacific Ocean and the first record from the tropical Eastern Pacific.